Study on heating capacity and heat loss of capillary radiant floor heating systems. (25th January 2020) - Ding, Pei; Li, Yanru; Long, Enshen; Zhang, Yin; Liu, Qinjian
Highlights: A new simplified calculation method for radiant floor was proposed. Calculated results agree well with measured and numerical simulated data. Floor equivalent thickness affect heating capacity varied with pipe spacing. Pipe wall with twice heat conductivity than filled layer can be ignored. Abstract: Radiant floor heating systems with the distinct advantages of low-temperature water supply, energy saving, uniform room temperature and well thermal comfort, are widely used in residential and office buildings in China. And those radiant floors embedded with capillary pipes have been increasing in popularity because of better thermal performance. In this paper, a new simplified calculation for heating capacity, heat loss and surface temperature of radiant heating floor with high-performance insulation layer was provided and validated by measured as well as numerical simulated data. By the simplified calculation method, the influence of each layer material on the heat transfer of capillary radiant heating floor have been analyzed and results show that, (1) the heating capacity will decreased with the increasement of pipe spacing and the descending slop is decided by the ratio of pipe spacing to the equivalent distance from pipes to the room environment; (2) thermal resistance of pipes could be ignored when it is twice more than that of filling material, or it will have negative influence on heating capacity with the increase of pipe spacing.